THE ALUMINIUM-COPPER-GRAPHITIC ALLOY, GOT AT MICROALLOYING BY FULLERENE C60 . - N. A. Svidunovich; D. V. Kuis; G. P. Okatova; A. P. Laskovnev (Литьë и металлургия, 2010)
Positive influence of small additives of fullerene on structure formation of aluminium-copper graphite alloy is determined.